(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
The countries of the Lower Maghreb (African) were distinguished during the fourth century AH / tenth century CE by a social pattern that is usual, traditional and distinct in some aspects, especially living, such as eating, drinking and clothing, in addition to the presence of organizational transactions concerned with setting the initial structure in the formation of the family and society and the steps involved in it related to engagement and marriage. There are dilemmas between the founders of the family and there are cases of divorce, which varied and took names in their presence.